2022
DOI: 10.3389/fcvm.2022.816387
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular and Prognostic Effect in Lesions With Different Stent Expansion During Primary PCI for STEMI: Insights From Coronary Physiology and Intravascular Ultrasound

Abstract: BackgroundWhile coronary stent implantation in ST-elevation myocardial infarction (STEMI) can mechanically revascularize culprit epicardial vessels, it might also cause distal embolization. The relationship between geometrical and functional results of stent expansion during the primary percutaneous coronary intervention (pPCI) is unclear.ObjectiveWe sought to determine the optimal stent expansion strategy in pPCI using novel angiography-based approaches including angiography-derived quantitative flow ratio (Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…There is an association between stent over-expansion and no reflow during initial PCI for ST-segment elevation myocardial infarction ( 20 ). Another recent study has provided further insight into the degree of stent expansion and MVD ( 21 ). In that study, evaluation of the impact of different degrees of stent expansion on microvascular function and the prognosis of primary PCI QFR-based IMR found that stent over-expansion (>100%) was an independent risk factor for no reflow and major adverse cardiovascular events, whereas 70–80% of slightly under-expanded stents was not a risk factor ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an association between stent over-expansion and no reflow during initial PCI for ST-segment elevation myocardial infarction ( 20 ). Another recent study has provided further insight into the degree of stent expansion and MVD ( 21 ). In that study, evaluation of the impact of different degrees of stent expansion on microvascular function and the prognosis of primary PCI QFR-based IMR found that stent over-expansion (>100%) was an independent risk factor for no reflow and major adverse cardiovascular events, whereas 70–80% of slightly under-expanded stents was not a risk factor ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study has provided further insight into the degree of stent expansion and MVD ( 21 ). In that study, evaluation of the impact of different degrees of stent expansion on microvascular function and the prognosis of primary PCI QFR-based IMR found that stent over-expansion (>100%) was an independent risk factor for no reflow and major adverse cardiovascular events, whereas 70–80% of slightly under-expanded stents was not a risk factor ( 21 ). In the present study, cases with no less than 80% stent expansion were included and those with over-expansion were excluded to avoid the influence of selection bias.…”
Section: Discussionmentioning
confidence: 99%